Strengthening Educational Administrator Competencies Through Internship Management: A Comparative Study in Indonesian Higher Education - Arifin, Zainal; Khurohman, Fatah; Sururi, Sururi; Nurillah, Salma (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The management of internship programs in Indonesian higher education continues to face structural and implementation challenges, particularly under the Merdeka Belajar Kampus Merdeka (MBKM) policy, which promotes experiential learning and inter-institutional collaboration. This study critically analyzes internship governance in two distinct academic settings: the Islamic Education Management (IEM) program at UIN Sunan Kalijaga Yogyakarta and the Educational Administration (EA) program at Universitas Pendidikan Indonesia Bandung. Drawing on Sondang Siagian’s five management functions-planning, organizing, directing, supervising, and evaluating-a qualitative case study approach was employed. Data were collected from purposively selected stakeholders, including program heads, field supervisors, and student interns (n = 18), using in-depth interviews, observations, and document analysis. The findings reveal two models of implementation: a structured two-phase system (IEM) and a flexible single-phase system (EA), both of which promote managerial, interpersonal, and technical competencies. However, shared obstacles persist, including irregular supervision, limited alignment with institutional needs, and evaluations focused primarily on summative outcomes. The IEM program excels in structured planning and alums mentoring, whereas the EA program demonstrates strengths in international collaboration and technical briefings. This study proposes a hybrid model that integrates structured planning with adaptive field practices, supported by formative evaluations and leadership training. Theoretically, the study contributes to the discourse on work-integrated learning by contextualizing internship governance within the framework of educational administration. Practically, it offers a replicable model for institutions seeking to align internship programs with MBKM policy objectives and labor market expectations. Future research is recommended to examine longitudinal impacts and incorporate alums and employer perspectives into internship assessments.